Pediatric otolaryngology: influence of ambulatorial surgical procedures on postoperative pain - de Sousa, Francisco Alves; Casanova, Maria Jorge; Pinto, Ana Nóbrega; Coutinho, Miguel Bebiano; e Sousa, Cecília Almeida (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: In Pediatric Otolaryngology surgery associating procedures is a common finding. Each surgical act elicits different degrees of pain, with implications on recovery. The aim of this work was to evaluate the severity of children’s pain after outpatient surgery, considering combinations of common Otolaryngologic procedures. Methods: Data from children submitted to surgery in the Pediatric ambulatory Unit of Centro Hospitalar Universitário do Porto was reviewed. Children with history of previous interventions or any associated comorbidity were excluded. Postoperative pain at hospital discharge using the Universal Pain assessment tool (0-10) was assessed and compared concerning the various procedures. Results: A total of 954 operated children were included. Adenoidectomy was performed in 783 patients (82.1%), tonsillectomy in 714 (74.8%), myringotomy in 432 (45.3%) and radiofrequency inferior turbinoplasty in 98 (10.3%). Patients undergoing tonsillectomy showed significantly higher pain scores (1.48±1.02 in tonsillectomy versus 0.89±0.75 in no tonsillectomy, p=0.001). Importantly, adenoid curettage, radiofrequency inferior turbinoplasty and myringotomy did not associate with increased post-operative pain (p>0.05). Number of procedures within the same intervention and surgical indication (recurrent infections, obstructive sleep disordered breathing and otitis media with effusion) did not influence post-operative pain scores (p>0.05). Conclusions: Performing total tonsillectomy was the most important influencer of post-operative pain in Pediatric ambulatory surgery in this cohort. Performing concomitant adenoidectomy, turbinoplasty or miringotomy do not seem to influence post-operative pain significantly. A higher number of procedures within the same intervention does not associate directly with postoperative pain scores.